Adaptive Torque Control for Process Optimization in Friction Stir Welding of Aluminum 6061-T6 Using a Horizontal 5-Axis CNC Machine - Austin Clark; Ihab Ragai (Journal of Manufacturing and Materials Processing, 2025)
The research presented herein investigates the impact of axial force and feed rate in the Friction Stir Welding (FSW) of aluminum alloy 6061-T6 in a GROB G552 horizontal 5-axis CNC machine with adaptive torque control enabled. The purpose of this study is to further advance the performance and characteristics of FSW aluminum alloys in 5-axis CNCs, particularly in conjunction with adaptive torque control. The Taguchi and ANOVA methods were utilized to define parameter tables and analyze the resulting data. Optical microscopy and tensile tests were performed on the welded samples to evaluate weld quality. The results from this study provide clear evidence that axial force has a significant effect on tensile strength in FSW AA6061-T6. The maximum UTS found in this study, welded with an axial force of 9.4 kN, retained 69% tensile strength of the base material. Conversely, a decrease in strength and an increase in void formation was found at higher feed rates with this force. Ideal welds, with minimal defects across all feed rates, were performed with an axial force of 8.3 kN. A feed rate of 300 mm/min at this force resulted in a 67% base metal strength. These findings contribute to improving joint strength and application efficiency in FSW AA6061-T6 performed in a horizontal 5-axis CNC machine where adaptive torque control is enabled.